Evaluation of virtual surgical planning and three‐dimensional configurations for reconstruction of maxillary defects using the fibula free flap. Issue 8 (14th September 2022) - Verdoy, Sergi Barrantes; Sadeghi, Payam; Ojeda, Anna López; Palacín Porté, José A.; Vinyals Vinyals, Joan M.; Barceló, Lia Huesa; Lluis, Enric Cisa; Compta, Xavier González; Diaz, Alberto Torres; Segú, Josep Oriol Bermejo
Abstract: Background: Maxillary reconstructive surgery with fibula free flaps (FFFs) is a challenging procedure for head and neck surgeons. However, virtual surgical planning (VSP) and three‐dimensional (3D) printing technologies have contributed to improved functional and aesthetic outcomes. The objective of this report is to demonstrate VSP/3D application in reconstruction of maxillary defects using the FFF by describing the different configurations available. We reviewed a series of consecutive cases operated at our institution and considered the management strategy of in‐house planning in VSP/3D application. Methods: In total, 11 cases were included from November 2016 to December 2021. Eight male and three female were included, with a mean age of 55.4 years old (range: 34–74 years old). Maxillary defects were classified according to Brown's Classification: two cases with IIB, one case with IIC, four cases with IID, three cases with III, and one case with IV. Preoperatively, facial computed tomography (CT) and lower extremity computed tomography angiogram (CTA) were performed in all patients. Osteocutaneous FFFs were planned, harvested, and customized according to the VSP/3D guide configuration. VSP and 3D printed cutting guides were performed by an external company in nine cases and were self‐planned in three of them. Titanium 3D‐printed fixation plates were used in four cases. Results: All flaps survived, and the main reconstructive goals were achieved in 9 cases out of 11. Mean FFF length before osteotomy was 20.0 cm (17.5–22.5 cm). None of the cases experienced flap ischemia or venous congestion. At least one complication occurred in four cases: Prefabricated titanium plate exposure (two cases), loss of donor site skin grafts (one case), and ectropion (one case). One patient underwent a second FFF reconstruction. Two titanium printed plates became exposed after radiotherapy and needed to be removed. Mean follow‐up time was 23.5 months (range 6–63 months). Dental rehabilitation was completed in eight of the 11 cases. Regarding functional recovery, five cases underwent delayed osseo‐integrated dental implants (ODI), and two cases had immediate ODI procedures. One case was treated with removal dentition. Conclusion: VSP/3D printing technology is a new and helpful tool to successful restoration of craniofacial function and aesthetics. It can be used in the broad range of configurations offered by FFFs considering our suggested management strategy.